Analisis Sistem Administrasi di Badan Usaha Milik Desa Wibawa Mukti Desa Sekarwangi Kabupaten Sumedang - Cahyani, Ayu; Supriatna, Adi; Somantri, Muhammad Siddiq; Yuningsih, Teti; Sudrajat, Arip Rahman (Mahesa Research Center, 2019)
The purpose of writing this research is to analyze the administration system which is carried out in the Village-Owned Enterprises in Sekarwangi Village. The method used in this research is descriptive analysis by first observing the relevant research object with a focus on observing the administration system which is carried out by the board administrator Village Owned Business. The location of the research is Sekarwangi Village, Buahdua District, Sumedang Regency. In conducting observations, there were three interviews with resource persons who were employees of the Village Owned Enterprises. Based on observations and interviews, the results showed that the administration system activities in the Village-Owned Enterprises were still low. This is caused by several factors including the lack of labor, lack of facilities and office infrastructure, low employee skills and minimal capital resources. This study concludes that in the management of Village-Owned Enterprises in Sekarwangi Village there are administrative activities that are not optimal and have not run well due to funding factors in the administrative system that have not been fulfilled either in personnel or in capital.